CHARACTERISING THE KEY ELEMENTS AFFECTING RBT TEACHERS’ COMPETENCE IN TVET EDUCATION IN PENANG - Suraya Zakaria; Siti Zuraidah Md Osman (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
In the subject of Design and Technology (RBT), the application of Information and Communication Technology (ICT) elements through technology applications can strengthen basic skills in a more effective learning process. Some issues arise as a result of the increase in technology, but there are gaps in the provision and support for teachers to adapt technology in their teaching. This study aims to identify the factors that cause RBT teachers to lack the skills to integrate technology into teaching practice and analyze the weaknesses of using technology in the classroom. Using qualitative research methods, five RBT teachers in Penang were interviewed. The results of the study found lack of knowledge, training and support, technology skills, as well as problems with devices and technology infrastructure to be the main obstacles. Despite the challenges, the findings of the study also show that the use of technology has great potential to increase the interest and effectiveness of teaching. This study suggests stakeholders to provide adequate equipment and more comprehensive training for RBT teachers. This study also contributes to the technology education literature by providing empirical evidence on the challenges faced as well as strategies to improve the use of technology in teaching.